Wayang Gedhog Sebagai Media Komunikasi Simbolik Dalam Upacara Rsi Gana Di Lombok - I Wayan Karang Astawa; I Wayan Wirata (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2020)
Puppet is one of the media used in communication process played by a puppeteer. The mastermind's expertise in performing shadow puppet, either as a performance or guidance greatly influences the message process that will be conveyed in the puppet show as a media of communication in delivering the meaning of the ritual of Rsi Gana in Lombok. The specific purpose of this research is to describe and analyze the form, function, and meaning of the mastermind's communication in the Gedhog shadow puppet. This research is conducted with a qualitative method, so that data analysis is carried out descriptively - qualitatively. This research was conducted in Lombok, at which the Rsi Gana ceremony followed by the Gedhog puppet. Communication with the mastermind of gedhog pupeet in communicating the meaning of the ceremony used the SMCR theory and Symbolic Intercionism Theory. Based on the results of the study it is known that the form of Gedhog puppet communication in delivering the meaning of Rsi Gana to the people in Lombok, 1) verbal communication and 2) forms of non-verbal communication, in conveying the messages contained in the story through pupeet figures and symbols in the puppet show that have the meaning associated with the ceremony accompanied, in this case is the Rsi Gana ceremony. The communicative function of gedhog puppeteer is to communicate the meaning of Rsi Gana to the people in Lombok 1) Social Functions, 2) Religious Functions, and 3) Functions of Instrumental or educational functions. Meaning of bedhog pupeet unication in communicating the meaning of Rsi Gana's ceremony through the characters of the shadow puppet performance 1) social meaning, 2) religious meaning, 3) meaning of education.